A Lateral AlGaN/GaN Diode with MIS-Gated Hybrid Anode for Ultra-Low Turn-On and High Breakdown Voltage. (1st January 2017) - Zhou, Qi; Shi, Yu; Dong, Changxu; Zhu, Liyang; Wei, Dong; Liu, Xiaosen; Chen, Wanjun; Zhang, Bo
Abstract : In this paper, we propose and experimentally demonstrate a novel lateral AlGaN/GaN diode on Si substrate. The diode features a recessed metal/Al2 O3 /III-nitride (MIS)-gated ohmic hybrid anode, in which the drive current can be well controlled by the MIS-Gate and flows between the two ohmic contacts from the anode to the cathode with substantially reduced overall on-resistance ( R on ). With this unique architecture, the forward turn-on voltage ( V T ) of the diode can be flexibly trimmed, which enables a record low V T of 0.2 V obtained in the proposed diode. The incorporation of high- k dielectric in the recessed gate region and the AlGaN back barrier realize significantly leakage current ( I leakage ) reduction yet high breakdown voltage ( BV ). The BV as high as 1100 V at I leakage less than 1 μ A/mm with drift length of 20 μ m is achieved in the proposed diode.